Educational issues in cartoons in the Saudi press - al - Sahli, Sawyer bint Zanaf bin Fawaz (Journal of Humanities & Social Sciences, 2017)
The main objective of the study was to identify the educational issues in Saudi journalism cartoons. Content analysis method (both qualitative and quantitative) has been used to identify the themes contained in the cartoons. Three Saudi newspapers were selected to be the study sample (okaz newspaper, Aljazeerah newspaper and Arriyadh newspaper). They published 210 cartoons about education during 2014. The results of the study showed that educational cartoons in Saudi newspapers only represented  6.433% that indicates low levels of concern on education issues in Saudi journalism cartoons. 48.571% of them discussed issues related to students, 26.667% discussed issues related to teachers, 13.333% discussed issues related to learning environment, and 6.190% discussed issues related to curriculum. Most of the cartoons portrayed male characters. Most of them were critical. The majority of the educational cartoons in Saudi newspapers came with comments or dialogues. Most of them were colored. The study recommended Saudi cartoonists to focus more on educational issues. The study suggested studying the role of cartoons in setting educational agenda.
Keywords: cartoons; Saudi journalism; educational issues